1997
DOI: 10.1152/jappl.1997.82.1.270
|View full text |Cite
|
Sign up to set email alerts
|

Training intensity, blood lipids, and apolipoproteins in men with high cholesterol

Abstract: Twenty-six hypercholesterolemic men (mean cholesterol, 258 mg/dl; age, 47 yr; weight, 81.9 kg) completed 24 wk of cycle ergometer training (3 days/wk, 350 kcal/session) at either high (n = 12) or moderate (n = 14) intensity (80 and 50% maximal O2 uptake, respectively, randomly assigned) to test the influence of training intensity on blood lipid and apolipoprotein (apo) concentrations. All physiological, lipid, and apo measurements were completed at 0, 8, 16, and 24 wk. Lipid data were analyzed via two x four r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 47 publications
4
34
0
2
Order By: Relevance
“…2 Crouse et al observed a greater increase in CRF in men exercising at high intensity as opposed to moderate intensity (measured via peak V O2) in middle-aged men (n=26) following 24 weeks of cycle ergometer exercise. 70 Similarly, O'Donovan et al observed a greater increase in CRF following 24 weeks of high-intensity ET in sedentary men (n=64) compared to moderate-intensity ET matched for ET energy costs. 71 In addition, several studies suggest that highintensity aerobic ET is associated with greater responses in glucose control, 72 insulin sensitivity, 73,74 and visceral fat loss 75 compared to moderate-intensity ET.…”
Section: Is Pa or Crf Level The Best Predictor Of CV Mortality?mentioning
confidence: 91%
“…2 Crouse et al observed a greater increase in CRF in men exercising at high intensity as opposed to moderate intensity (measured via peak V O2) in middle-aged men (n=26) following 24 weeks of cycle ergometer exercise. 70 Similarly, O'Donovan et al observed a greater increase in CRF following 24 weeks of high-intensity ET in sedentary men (n=64) compared to moderate-intensity ET matched for ET energy costs. 71 In addition, several studies suggest that highintensity aerobic ET is associated with greater responses in glucose control, 72 insulin sensitivity, 73,74 and visceral fat loss 75 compared to moderate-intensity ET.…”
Section: Is Pa or Crf Level The Best Predictor Of CV Mortality?mentioning
confidence: 91%
“…98 ± 101 A recent report by Crouse et al 102 suggests that changes in blood lipids in hypercholesterolemic men are not in¯uenced by exercise intensity when the caloric expenditure of the exercise programs are held constant. In contrast to an extensive literature on HDL-C and physical activity in able-bodied samples the literature regarding the eect of physical activity on HDL-C in SCI subjects is limited to four cross-sectional studies of physical activity and HDL-C, 13,24,31,103 three reports on the cross-sectional association between cardiovascular ®tness and HDL-C 29,31,104 and one exercise training study.…”
Section: Physical Activity and Hdlmentioning
confidence: 99%
“…Thus, the value of regular aerobic exercise in increasing serum HDL-C level and in reducing the risk of CVD has received widespread acceptance (Rippe et al, 1988). In contrast, results of aerobic exercise studies vary considerably, depending on the exercise program (eg, duration, intensity, or frequency) and characteristics of subjects at baseline (Crouse et al, 1997 Comparisons between intensities of aerobic exercise programs resulted in favorable effects only for high intensity. The most frequently observed alteration was an increase in the high-density lipoprotein cholesterol, whereas reductions in triglycerides, total cholesterol, and low-density lipoprotein cholesterol appeared less often (Tambalis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%